A STUDY OF PROBLEM-SOLVING ABILITY IN PHYSICS AMONG INTERMEDIATE LEVEL STUDENTS - Agarwal, Rashmi; Gupta, Sanjeev Kumar (SCHOOL SCIENCE, 2010)
This study attempts to assess the problem-solving ability in physics among intermediate level students in relation to their sex, locality and type of school. To execute the present study, 500 students studying physics in Class XII from 30 schools of Rohilkhand region were selected on basis of multi stage random sampling technique. The present study was conducted through survey method. The data were analysed by mean, S.D. and ‘t’ test. The findings indicate that sex and type of school both influenced the physics problem-solving ability of the students. Students of privately-managed and girl students have better physics problem-solving ability than their respective counterparts. However, locality does not reflect the significance effect over physics problem-solving ability of the students.